2016
DOI: 10.1002/mame.201600296
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Bonding of an Electroconductive Hydrogel to Gold‐Coated Titanium Surfaces via Thiol‐ene Click Chemistry

Abstract: In the present study, the covalent bonding of electroconductive cross‐linked hydrogel networks with both electro‐properties and hydrogel characteristics to titanium surfaces via a UV‐initiated radical thiol‐ene click reaction is investigated. The electroconductive hydrogel layers are formed by the electropolymerization of pyrrole within the titanium implant‐supported gelatin methacrylate hydrogel. Characterization of the surface morphology of the layers reveals a unique rough macroporous structure. The hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 35 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Collagen, as a well-established hydrogel raw material, exhibits biocompatibility, biodegradability, and does not produce any harmful residues, increasing its attractiveness for tissue engineering and regenerative medicine applications [103]. Wound healing [42,43]; Cornea regeneration [71] Gelatin / Cu-AAC reaction [72,73]; DA reaction [74][75][76]; SPAAC reaction [27]; radical mediated thiol-ene reaction [77][78][79][80]; Schiff base reaction [38]; thiol-Michael reaction [12] Wound healing [36]; Bone regeneration [38]; Spinal cord regeneration [8]; Cornea regeneration [12,71] Silk protein Cu-AAC reaction [72]; Schiff base reaction [37,[39][40][41]85]; Radical mediated thiol-ene reaction [86]; DA reaction [76,87]; Oximeforming reaction [31]; thiol-Michael reaction [85,88] Wound healing [37]; Spinal cord regeneration [39][40][41]; Cartilage regeneration [88]; Cornea regeneration [11] Alginate Schiff base reaction [5,25,89,90]…”
Section: Collagenmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen, as a well-established hydrogel raw material, exhibits biocompatibility, biodegradability, and does not produce any harmful residues, increasing its attractiveness for tissue engineering and regenerative medicine applications [103]. Wound healing [42,43]; Cornea regeneration [71] Gelatin / Cu-AAC reaction [72,73]; DA reaction [74][75][76]; SPAAC reaction [27]; radical mediated thiol-ene reaction [77][78][79][80]; Schiff base reaction [38]; thiol-Michael reaction [12] Wound healing [36]; Bone regeneration [38]; Spinal cord regeneration [8]; Cornea regeneration [12,71] Silk protein Cu-AAC reaction [72]; Schiff base reaction [37,[39][40][41]85]; Radical mediated thiol-ene reaction [86]; DA reaction [76,87]; Oximeforming reaction [31]; thiol-Michael reaction [85,88] Wound healing [37]; Spinal cord regeneration [39][40][41]; Cartilage regeneration [88]; Cornea regeneration [11] Alginate Schiff base reaction [5,25,89,90]…”
Section: Collagenmentioning
confidence: 99%
“…However, the low stiffness of physical cross-linked gelatin hydrogels limits their application in regenerative medicine. Consequently, click chemical cross-linking methods including Cu-AAC reaction [72,73], DA reaction [74][75][76], and radical mediated thiol-ene reaction [77][78][79][80], have been employed to enhance the stiffness of gelatin hydrogels. For example, Hu et al introduced alkynyl groups into gelatin, using propiolic acid to modify it [72].…”
Section: Gelatinmentioning
confidence: 99%
“…Although tough and robust hydrogels have been developed, the weak interfacial bindings between hydrogels and elastomers severely limit their integration and multifunctionality . Various research groups reported a strategy to create stable adhesion of the hydrogel‐elastomer layers via covalent chemical anchorage . Lee et al established robust adhesion by chemical bonding between the contact material PDMS and hydrogel electrode with benzophenone treatments to develop skin attachable ionic communicators based on TENGs…”
Section: Self‐powered Ionic Tactile Sensorsmentioning
confidence: 99%